Practice and Policy Implecations of Quality Assurance and Accreditation: A Review - Gautam, Tara Prasad; Mishra, Anjay Kumar; Shailashri , V. T. (GS WOW: Wisdom of Worthy Research Journal, 2025)
Nepal’s higher education sector has expanded significantly since the 1990s; however, this growth has not been paralleled by improvements in institutional quality, governance, or accountability.. But this increase has not been matched by better institutional quality, governance, or accountability. The University Grants Commission (UGC) of Nepal came up with the Quality Assurance and Accreditation (QAA) system in 2007 to deal with these problems. Following PRISMA 2020 guidelines, a systematic review was conducted using sources from Scopus, Web of Science, Google Scholar, UGC Nepal databases, and institutional repositories. We chose 42 research, including peer-reviewed journal articles, policy documents, and institutional reports published between 2005 and 2024, based on certain criteria and then used the CASP and GRADE rating frameworks to rate them. We used NVivo software to code and analyze the themes. Only 3% of Nepal’s colleges and universities were completely accredited as of 2024. Nepal lags behind when it comes to making ensuring that quality assurance is in line with performance indicators, outcome-based education, and participatory government. This shift from symbolic accreditation to progressive, participatory QA is particularly crucial for making higher education more trustworthy, helping graduates find jobs, and giving Nepalese higher education institutions a bigger role in the country’s growth. The results are particularly essential for politicians, academic leaders, and quality assurance professionals who wish to make big improvements to Nepal’s higher education system.